Photosynthesis in dynamic light: systems biology of unconventional chlorophyll fluorescence transients in Synechocystis sp. PCC 6803 - Nedbal, Ladislav; Brezina, Vítezslav; Cervený, Jan; Trtílek, Martin (Photosynthesis research, 2005)
Photosynthetic organisms live in a dynamic environment where light typically fluctuates around a mean level that is slowly drifting during the solar day. We show that the far-from-equilibrium photosynthesis occurring in a rapidly fluctuating light differs vastly from the stationary-flux photosynthesis attained in a constant or slowly drifting light. Photosynthetic organisms in a static or slowly drifting light can be characterized by a steady-state quantum yield of chlorophyll fluorescence emission F' that is changing linearly with small and slow variations of the incident irradiance I+DeltaI(t): F'(I+DeltaI(t)) approximately Fmean '(dF)/(dI).DeltaI(t). In Synechocystis sp. PCC 6803, the linear approximation holds for an extended interval covering largely the static irradiance range experienced by the cyanobacteria in nature. The photosynthetic dynamism and, consequently, the dynamism of the chlorophyll fluorescence emission change dramatically when exposing the organism to a fluctuating irradiance. Harmonically-modulated irradiance I+DeltaI . sin(2pit/T), T approximately 1-25 s induces perpetual, far-from-equilibrium forced oscillations that are strongly non-linear, exhibiting significant hysteresis with multiple fluorescence levels corresponding to a single instantaneous level of the incident irradiance. We propose that, in nature, the far-from-equilibrium dynamic phenomena represent a significant correction to the steady-state photosynthetic activity that is typically investigated in laboratory. Analysis of the forced oscillations by the tools of systems biology suggests that the dynamism of photosynthesis observed in fluctuating light can be explained by a delayed action of regulatory agents.
Keywords: Synechocystis; Systems Biology; Photosystem I Protein Complex; fotosyntéza; Photosynthesis; Energy Transfer; Chlorophyll; Nonlinear Dynamics; transport elektronů; fotosystém I (proteinový komplex); přenos energie; Fluorescence; světlo; Time Factors; Electron Transport; chlorofyl; časové faktory; Photosystem II Protein Complex; nelineární dynamika; Light; systémová biologie; fluorescence; fotosystém II (proteinový komplex)